From Lived Space to Tourist Attraction: The Comodification of Old Houses in Kayutangan Village, Malang City - Daratirta, Dina; Nurhadi, Iwan; Fatma Chawa, Anif (Graduate School, Universitas Brawijaya, 2026)
This study aims to uncover the commodification of residents' living spaces in Kampung Kayutangan, Malang City, through the transformation of old houses into heritage tourism attractions. The change of the village into a tourist destination shifts the function of houses from domestic space to tourist consumption space. This study offers a novel approach by shifting the focus of heritage tourism studies from a predominance of architectural and physical analysis of buildings to the lived experiences, power relations, and social consequences experienced by residents inhabiting the spaces surrounding heritage buildings that have been developed as tourist destinations. This study aims to analyze the social dynamics in heritage tourism practices, particularly the exclusion of local narratives and the ambivalence between lived space and display space. This study draws on Michael Herzfeld's (2015) thinking on heritage and power to examine commodification, knowledge inequality, and the tension between preservation and economic exploitation. The method used is qualitative with a case study approach through observation, interviews, and documentation. The results of the study show the dominance of official narratives by authorized actors, as well as the commodification of old houses, which affects changes in social practices, the disruption of private space, and latent conflicts at the community level. This study confirms that heritage tourism is an arena for negotiating meaning, identity, and power in urban spaces.